The 3G IP multimedia subsystem (IMS) : merging the Internet and the cellular worlds - Camarillo, Gonzalo (J. Wiley & Sons, 2008)
Third edition of this best-selling guide to IMS: fully revised, and updated with brand new material. The IMS (IP Multimedia Subsystem) is the technology that merges the Internet with the cellular world. It makes Internet technologies such as the web, email, instant messaging, presence, and videoconferencing available nearly everywhere at any time. The third edition of this bestselling book is fully updated and provides comprehensively expanded content, including new chapters on emergency calls and on Voice Call Continuity (VCC). As well as this, The 3G IP Multimedia Subsystem (IMS) presents up.